2009
DOI: 10.1021/ja807666d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and the Failure of Transition State Theory in Alkene Hydroboration

Abstract: Transition state theory fails to accurately predict the selectivity in an example where it is ubiquitously invoked, hydroboration. The hydroboration of terminal alkenes with BH 3 is moderately regioselective, affording an 88:12 -90:10 ratio of anti-Markovnikov:Markovnikov adducts. Highlevel ab initio calculations predict too large of an energy difference between anti-Markovnikov and Markovnikov transition structures to account for the observed product ratio, and the consideration of calculational error, solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
161
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(172 citation statements)
references
References 16 publications
(20 reference statements)
6
161
0
1
Order By: Relevance
“…This is formed in an exothermic bimolecular step after dissociation of the ether solvent from the borane, and is thereby initially formed with excess internal energy, of roughly 11 kcal/mol. 117 From this common intermediate, reaction can proceed over two different transition states, one leading to the primary borane, and one to the secondary isomer. Because both barriers are very low, reaction proceeds very rapidly, in several ps.…”
Section: Master Equation Treatment Of Solutionphase Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is formed in an exothermic bimolecular step after dissociation of the ether solvent from the borane, and is thereby initially formed with excess internal energy, of roughly 11 kcal/mol. 117 From this common intermediate, reaction can proceed over two different transition states, one leading to the primary borane, and one to the secondary isomer. Because both barriers are very low, reaction proceeds very rapidly, in several ps.…”
Section: Master Equation Treatment Of Solutionphase Reactionsmentioning
confidence: 99%
“…Indeed, there is some suggestion that the reaction has partial ballistic or dynamical character, with barrier crossing occurring impulsively immediately without any vibrational energy randomization within the intermediate. 117 This was suggested to account for the observed ratio of the two isomers, of roughly 9:1, which differs significantly from the 99:1 ratio expected for a thermal reaction, based on accurate quantum chemical calculations that yield a difference in standard free energies for the two competing TSs of 2.5 kcal/mol. However, it is also possible to account for the observed ratio of products by taking into account the incomplete thermalization of the intermediate.…”
Section: Master Equation Treatment Of Solutionphase Reactionsmentioning
confidence: 99%
“…[20][21][22] For example, there is good evidence that thermal reactions as well-known as alkene hydroboration have a Markovnikov/AntiMarkovnikov product ratio which is determined by the extent of nascent vibrational excitation in the short lived addition complex. 12,23 Recently, it has even been suggested that solute/solvent interactions which take place in the course of transient vibrational relaxation dynamics provide a route to enantioselective amplification. 19 Accurately simulating reaction dynamics in coupled solute/solvent environments remains a challenge within the field of computational and theoretical chemistry, 14,16,[24][25][26] mostly owing to the fact that it is difficult to construct a potential energy surface (PES) whose balanced accuracy and efficiency is sufficient to interpret experiments.…”
Section: Introductionmentioning
confidence: 99%
“…1 and assuming a kinetically controlled mechanism, we can predict the most favorable isomers computationally [21,22]. Previous computational studies have also pointed out the fact that the final thermodynamically favored products might not reflect the selectivity of the kinetically favored hydroboration reactions [23] and emphasized the importance of dynamical effects beyond transition state theory [24][25][26].…”
Section: Monohydroboration Products Of Dienesmentioning
confidence: 90%